SYMPK Is Required for Meiosis and Involved in Alternative Splicing in Male Germ Cells - Wu, Rui; Zhan, Junfeng; Zheng, Bo; Chen, Zhen; Li, Jianbo; Li, Changrong; Liu, Rong; Zhang, Xinhua; Huang, Xiaoyan; Luo, Mengcheng (Frontiers in Cell and Developmental Biology, 2021)
SYMPK is a scaffold protein that supports polyadenylation machinery assembly on nascent transcripts, and is also involved in alternative splicing in some mammalian somatic cells. However, the role of SYMPK in germ cells remains unknown. Here, we report that SYMPK is highly expressed in male germ cells, and germ cell specific knockout (cKO) of Sympk in mouse leads to male infertility. Sympk cKODdx4-cre mice showed reduced spermatogonia at P4 and almost no germ cells at P18. Sympk cKOStra8-Cre spermatocytes exhibit defects in homologous chromosome synapsis, DNA double strand breaks (DSB) repair, and meiotic recombination. RNA-seq analyses reveal that SYMPK is associated with alternative splicing, besides regulating many genes expression in spermatogenic cells. Importantly, Sympk deletion results in abnormal alternative splicing and decreased expression of Sun1. Taken together, our results demonstrate that SYMPK is pivotal for meiotic progression by regulating pre-mRNA alternative splicing in male germ cells.